A interação entre Caxias e Inhaúma no Rio Paraguai - Armando de Senna Bittencourt (Navigator)
When the Marquis Caxias was assigned to the position of Commander in Chief of all Brazilian Forces, he chose the Fleet Commander Joaquim José Ignácio to be in charge of the Brazilian armada. The perfect understanding and cooperation between the Marquis of Caxias and the Viscount of Inhaúma was of fundamental importance to the success achieved in this war, and is to be the object of analysis in this paper.